Increased T-cell responses to Epstein–Barr virus with high viral load in patients with Epstein–Barr virus-positive diffuse large B-cell lymphoma. Issue 4 (April 2015) - Morishima, Satoko; Nakamura, Shigeo; Yamamoto, Kazuhito; Miyauchi, Hidemasa; Kagami, Yoshitoyo; Kinoshita, Tomohiro; Onoda, Hiroshi; Yatabe, Yasushi; Ito, Masafumi; Miyamura, Kouichi; Nagai, Hirokazu; Moritani, Suzuko; et al.
Abstract The immunological status of patients with Epstein–Barr virus-positive diffuse large B-cell lymphoma (EBV+ DLBCL) without obvious immunodeficiency has not been elucidated. A multicenter prospective study was conducted to assess pretreatment T-cell responses to EBV, EBV-DNA load and anti-EBV antibody in these patients. The proliferative and interferon (IFN)-γ-producing capacity of T-cells in response to autologous B-lymphoblastoid cell lines was determined using carboxyfluorescein diacetate succinimidyl ester (CFSE)-based assay. Frequencies of EBV-specific CD4+ T-cells in patients with EBV+ DLBCL (n = 13) were significantly higher than in healthy controls (HCs) (n = 16) after both ex vivo and in vitro stimulation. Frequencies of EBV-specific CD8+ T-cells in patients with EBV+ DLBCL tended to be higher than in HCs after in vitro stimulation. Patients with EBV+ DLBCL also showed increased immunoglobulin G (IgG) responses to lytic EBV-encoded antigens. Pretreatment plasma EBV-DNA level was significantly higher in patients with EBV+ DLBCL than in patients with EBV− DLBCL or HCs. In conclusion, EBV-specific T-cells showed increased reactivity, accompanied by higher levels of plasma virus DNA in patients with EBV+ DLBCL.